Análisis de sustentabilidad en sistemas de producción agropecuaria un enfoque de revisión bibliográfica. - Vargas Salazar, Luis Xavier (2021)
This research is based on a bibliographic review of scientific articles with the topic related to "SUSTAINABILITY ANALYSIS IN AGRICULTURAL PRODUCTION SYSTEMS," for which the SCImago Journal Rank (acronym SJR) platform was used as a tool that allows the researcher to identify whether the articles belong to a certain quartile and their respective H index. Also, the MENDELEY bibliographic manager software was downloaded to save the information, which facilitates the search and retrieval of articles or essential documents, many of them with access to the full text. The methodologies that have been applied, such as the MESMIS methodology, barometer, and indicators are analyzed in the articles; this shows that the projects constantly change; subsequently, they must have the capacity to be productive of self-regulators and transform themselves without losing their functionality.Finally, it was shown that for the subject of sustainability, it must always comply with the three laws such as environment, economy, society. Also, the most reliable methodology is MESMIS since sustainability is an investment in innovation through productivity scenarios, competitiveness, and sustainability. Moreover, it is shown that Latin American countries such as Mexico, Colombia, Chile are the ones that carry out the most projects or research about sustainability.